Pembuatan Alat Uji Putaran Kritis Poros - Jufrizal, Ryan; Mukhnizar, Mukhnizar; Afdal , Afdal; Abu , Risal; Zulkarnain , Zulkarnain (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This critical shaft rotation test tool is used to calculate the maximum deflection of a steel shaft. Currently, the critical shaft rotation test tool still uses human power to operate it, namely by rotating the handle to read the rotation value. So the test results carried out are not effective and accurate. This tool uses an electric motor with ¼ HP power and 2800 Rpm rotation as the driving force. So that the results are more accurate, this tool is designed to use an electronic system (sensor) equipped with a digital counter. Making this critical rotation test tool for the shaft goes through several processes, namely, making a table or position of the critical rotation test tool for the shaft using a digital counter, selecting the disk (load), selecting the bearing (pillow block), selecting the electric motor, selecting the shaft, and selecting the voltage regulator. . The testing phase has undergone several testing stages and the results are as planned. The tool that has been made can be operated effectively and obtain results as planned, and its operation is very easy.